How fast was the Matuyama-Brunhes geomagnetic reversal? A new subcentennial record from the Sulmona Basin, central Italy - Sagnotti, Leonardo; Giaccio, Biagio; Liddicoat, Joseph C.; Nomade, Sebastien; Renne, Paul R.; Scardia, Giancarlo [UNESP]; Sprain, Courtney J. (Oxford Univ Press, 2016)
A recent study of the Matuyama-Brunhes (M-B) geomagnetic field reversal recorded in exposed lacustrine sediments from the Sulmona Basin (Italy) provided a continuous, high-resolution record indicating that the reversal of the field direction at the terminus of the M-B boundary (MBB) occurred in less than a century, about 786 ka ago. In the sediment, thin (4-6 cm) remagnetized horizons were recognized above two distinct tephra layers-SUL2-19 and SUL2-20-that occur similar to 25 and similar to 35 cm below the MBB, respectively. Also, a faint, millimetre-thick tephra (SUL2-18) occurs 2-3 cm above the MBB. With the aim of improving the temporal resolution of the previous Sulmona MBB record and understanding the possible influence of cryptotephra on the M-B record in the Sulmona Basin, we performed more detailed sampling and analyses of overlapping standard and smaller samples from a 50 cm-long block that spans the MBB. The new data indicate that (i) the MBB is even sharper than previously reported and occurs similar to 2.5 cm below tephra SUL2-18, in agreement with the previous study; (ii) the MBB coincides with the rise of an intensity peak of the natural remanent magnetization (NRM) intensity, which extends across SUL2-18; (iii) except for a 2-cm-thick interval just above tephra SUL2-18, the rock magnetic parameters (k, ARM, M-r, M-s, B-c, B-cr) indicate exactly the same magnetic mineralogy throughout the sampled sequence. We conclude that either SUL2-18 resulted in the remagnetization of an interval of about 6 cm (i.e. during the NRM intensity peak spanning similar to 260 +/- 110 yr, according to the estimated local sedimentation rate), and thus the detailed MBB record is lost because it is overprinted, or the MBB is well recorded, occurred abruptly about 2.5 cm below SUL2-18 and lasted less than 13 +/- 6 yr. Both hypotheses challenge our understanding of the geomagnetic field behaviour during a polarity transition and/or of the NRM acquisition process in the Sulmona lacustrine sediment.
Keywords: Palaeomagnetic secular variation; Rapid time variations; Reversals: process, time scale, magnetostratigraphy; Rock and mineral magnetism